Allelic variation of the rice blast resistance gene Pid3 in cultivated rice worldwide - Lv, Qiming (Sci Rep, 2017)
In this study, the re-sequencing data from 3,000 rice genomes project (3 K RGP) was used to analyze the allelic variation at the rice blast resistance (R) Pid3 locus. A total of 40 haplotypes were identified based on 71 nucleotide polymorphic sites among 2621 Pid3 homozygous alleles in the 3k genomes. Pid3 alleles in most japonica rice accessions were pseudogenes due to premature stop mutations, while those in most indica rice accessions were identical to the functional haplotype Hap_6, which had a similar resistance spectrum as the previously reported Pid3 gene. By sequencing and CAPS marker analyzing the Pid3 alleles in widespread cultivars in China, we verified that Hap_6 had been widely deployed in indica rice breeding of China. Thus, we suggest that the priority for utilization of the Pid3 locus in rice breeding should be on introducing the functional Pid3 alleles into japonica rice cultivars and the functional alleles of non-Hap_6 haplotypes into indica rice cultivars for increasing genetic diversity.